Tough thiourethane thermoplastics for fused filament fabrication. Issue 6 (13th October 2017) - Ellson, Gregory; Carrier, Xavier; Walton, Jamie; Mahmood, Samsuddin Faisal; Yang, Kejia; Salazar, Joshua; Voit, Walter E.
ABSTRACT: Fused filament fabrication (FFF) is the most common form of additive manufacturing. Most FFF materials are variants of commercially available engineering plastics. Their performance when printed can widely vary, thus there is an increasing volume of research on alternative materials with thermal and mechanical performance optimized for FFF. In this work, thiol–isocyanate polymerization is used for the development of a one‐pot synthesis for polythiourethane thermoplastics for tough three‐dimensional (3D) printing applications. The thiol–isocyanate reaction mechanism allows for rapid polymer synthesis with minimal byproduct formation and few limitations on reaction conditions. The resulting elastomer has high toughness and a low melting point, making it favorable for use as a 3D printing filament. The elastomer outperforms commercial filaments in tension when printed. Considering the rapid advancement of additive manufacturing and the limitations of many engineering polymers with the 3D printing process, these results are encouraging for the development of bespoke 3D printing thermoplastics. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45574. Abstract :